2019
DOI: 10.1080/21645515.2019.1589287
|View full text |Cite
|
Sign up to set email alerts
|

Trends in vaccine investment in middle income countries

Abstract: Although a proven and effective preventive health measure, childhood immunization programs remain vulnerable to budgetary pressures. Sustainable financing of immunization programs is an important issue that presents a challenge for middle-income countries (MIC) in particular, in part due to technological advances meaning more vaccines are available. This study aimed to analyse trends in immunization program investment across 15 MIC selected based on availability of data, income level classification, and region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…However, Krishnamoorthy et al (2019) highlights that the Indian government currently spends only 2% of the healthcare budget on immunization programs, and therefore vaccination spending will need to increase to maintain any ongoing or future PCV programs [ 20 ]. This finding is consistent with other countries where vaccine spending often lags behind overall health spending, limiting access to critical preventative health measures [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, Krishnamoorthy et al (2019) highlights that the Indian government currently spends only 2% of the healthcare budget on immunization programs, and therefore vaccination spending will need to increase to maintain any ongoing or future PCV programs [ 20 ]. This finding is consistent with other countries where vaccine spending often lags behind overall health spending, limiting access to critical preventative health measures [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…477 More recent data shows that out of the countries selected, vaccines accounted for less than 2% of total healthcare spending. 478 Another similar analysis of countries found that not one of them spent more than 0.5% of its healthcare budget on vaccines. 479 Vaccine payments may not be enough to cover the costs of producing them and it was calculated that in the US, 79% of vaccination payments fell short.…”
Section: Homogeneity Of Tactics Techniques and Tropesmentioning
confidence: 99%
“…Despite the large burden of pneumococcal disease, many countries in Asia have yet to implement PCVs into NIPs, in contrast to countries in North America and Europe [4]. One contributing factor to this lag in immunization coverage is that low-middle income countries (LMIC) and middle-income countries (MIC) face substantial funding constraints in expanding immunization programs [5]. However, while LMIC receive substantial financial support to expand immunization programs through Gavi, The Vaccine Alliance, MICs have not expanded immunization budgets to fund all recently licensed vaccines [5].…”
Section: Article Highlightsmentioning
confidence: 99%